PENGARUH MNEMONIC TERHADAP DAYA INGAT DAN KEMAMPUAN BERPIKIR KRITIS MENGENAI UKURAN DISPERSI SEBARAN DATA - Veneranda Suri Mappan; Edy Tandililing; Ahmad Yani (Universitas Tanjungpura, 2020)
AbstractThis research was directed to reach some goals. First Measuring the memory of students in learning about the size of the dispersion of data distribution before and after learning with the help of mnemonics. Second was to measuring students' critical thinking skills in learning about data dispersion measures after learning with the help of mnemonics.In data collection, the methods used is True Experiment while the form of research used is experimental. Mnemonic exploration results in the form of the letter V pattern can be used on several materials at once. The first pattern is used to solve the median, quartile, decile and percentile while the second pattern is only used for mode lesson. The average post test of the experimental groups memory is 68.972 with 47.8% completeness which is still better when compared to the conventional learning completeness average which is only able to reach 43.5%. The value of t count 0.8502 is smaller than t table that is 1.7139.Post test data analyzed using the independent sample t test has a tendency to decrease while the post test data analyzed using the separated variance test is accepted.Keywords: Deciles, Median, Mnemonic, Mode, Pattern V, Percentile, Quartiles